Lectures on Evolution : Essay #3 from "Science and Hebrew Tradition" - Huxley, Thomas Henry, 1825-1895 (Salt Lake City, UT : Project Gutenberg, 2001)
"Lectures on Evolution" by Thomas Henry Huxley is a scientific exploration written during the late 19th century. The book delves into the various hypotheses regarding the history of life on Earth, emphasizing the concept of evolution as it relates to natural history and the development of species over time. At the start of this work, Huxley presents readers with an intricate discussion of three main hypotheses about the history of nature: the eternity of the present state, the Miltonic hypothesis of sudden creation, and the evolutionary hypothesis. Each hypothesis is accompanied by a critical examination of its implications, strengths, and weaknesses using scientific reasoning and historical evidence. Huxley highlights the necessity for a scientific basis to understand the continuity of life and evolutionary processes rather than relying on anecdotal or purely theoretical assumptions. The opening portion sets the stage for a deeper investigation into the evidence for evolution and its implications for understanding the natural world. (This is an automatically generated summary.)
Release date is 2001-05-01
Produced by D. R. Thompson, and David Widger
Keywords: Science; Evolution; Bible and science; Paleontology